Routine screening of emergency admissions at risk of chronic hepatitis (SEARCH) identifies and links hepatitis B cases to care. (14th September 2022) - Jacob, Rachael; Prince, David S.; Pipicella, Joseph L.; Nguyen, Angela; Bagatella, Melissa; Alvaro, Frank; Maley, Michael; Foo, Hong; Middleton, Paul; Kayes, Tahrima; DiGirolamo, Julia; Davison, Scott A.; et al.
Abstract: Background and Aims: Significant barriers exist with hepatitis B (HBV) case detection and effective linkage to care (LTC). The emergency department (ED) is a unique healthcare interaction where hepatitis screening and LTC could be achieved. We examined the efficacy and utility of automated ED HBV screening for Overseas Born (OB) patients. Methods: A novel‐automated hepatitis screening service "SEARCH" (Screening Emergency Admissions at Risk of Chronic Hepatitis) was piloted at a metropolitan hospital. A retrospective and comparative analysis of hepatitis testing during the SEARCH pilot compared to a period of routine testing was conducted. Results: During the SEARCH pilot, 4778 OB patients were tested for HBV (86% of eligible patient presentations), compared with 1.9% of eligible patients during a control period of clinician‐initiated testing. SEARCH detected 108 (2.3%) hepatitis B surface antigen positive patients including 20 (19%) in whom the diagnosis was new. Among 88 patients with known HBV, 57% were receiving medical care, 33% had become lost to follow‐up and 10% had never received HBV care. Overall, 30/88 (34%) patients with known HBV were receiving complete guideline‐based care prior to re‐engagement via SEARCH. Following SEARCH, LTC was successful achieved in 48/58 (83%) unlinked patients and 19 patients were commenced on anti‐viral therapy. New diagnoses of cirrhosis and hepatocellular carcinoma were made in five and one patient(s) respectively. Conclusions: Automated ED screening of OB patients is effective in HBV diagnosis, re‐diagnosis and LTC. Prior to SEARCH, the majority of patients were not receiving guideline‐based care.